Legal Dialectics: Age Limits for Marriage and Political Rights in Indonesia - Sarip Sarip; Diana Fitriana; Aip Syarifudin; Ali Romdoni; Multahibun Multahibun (Universitas Ahmad Dahlan, 2022)
Introduction: This study aimed to examine the legal dialectic over the age limit for marriage and political rights in Indonesia. It was promoted by a new marriage regulation stipulating the minimum age of nineteen years for men and women. This regulation correlates with the rules containing the minimum age limit, necessitating a further discussion.Objective: Previous studies on the minimum age limit did not focus on the law dialectic.Methodology: There are contradictions between the normative method of law and the idea of legal dialectics. The conclusions were drawn inductively.Findings: There are inequalities in several laws and regulations over the minimum age. The legal products, including a minimum age, are specific to certain laws and actions. The marriage dispensation has broken through higher laws, significantly impacting political rights. Therefore, positive law that ideally becomes a thesis turns into an antithesis due to the dispensation.Paper Type: Research Article